Alysicarpus ovalifolius (Fabaceae, Desmodieae), a new record for the ﬂora of Brazil - Hassemer, Gustavo; Ferreira, João Paulo R.; Funez, Luís A. (Iheringia, Série Botânica., 2018)
Alysicarpus ovalifolius (Schumach. & Thonn.) J. Léonard is a legume species used as forage plant, which is originally native to Africa but today has a pantropical distribution. This species is probably expanding its distribution in the neotropics and therefore can be considered a potentially invasive species. In Brazil, the only species of Alysicarpus Neck. ex Desv. hitherto recorded was A. vaginalis (L.) DC., which is also non-native in the Americas. This study presents the fi rst account of the occurrence and distribution of A. ovalifolius in Brazil, including notes on its taxonomic status and potential invasiveness. Brazilian specimens of A. ovalifolius had been so far misidentifi ed as A. vaginalis. We also present here the fi rst records of the genus Alysicarpus in Santa Catarina state, southern Brazil, and provide an identifi cation key to the two species of Alysicarpus that occur in Brazil.